Ag- but Not ZnO-Nanoparticles Disturb the Airway Epithelial Barrier at Subtoxic Concentrations - Helena Moratin; Anna Thöle; Josephine Lang; Totta Ehret Kasemo; Manuel Stöth; Rudolf Hagen; Agmal Scherzad; Stephan Hackenberg (MDPI AG, 2023)
Inhalation is considered to be the most relevant source of human exposure to nanoparticles (NPs); however, only a few investigations have addressed the influence of exposing the respiratory mucosal barrier to subcytotoxic doses. In the nasal respiratory epithelium, cells of the mucosa represent one of the first contact points of the human organism with airborne NPs. Disruption of the epithelial barrier by harmful materials can lead to inflammation in addition to potential intrinsic toxicity of the particles. The aim of this study was to investigate whether subtoxic concentrations of zinc oxide (ZnO)- and silver (Ag)-NPs have an influence on upper airway barrier integrity. Nasal epithelial cells from 17 donors were cultured at the air-liquid interface and exposed to ZnO- and Ag-NPs. Barrier function, quantified by transepithelial electrical resistance (TEER), decreased after treatment with 10 µg/mL Ag-NPs, but FITC-dextran permeability remained stable and no change in mRNA levels of tight junction proteins and E-cadherin was detected by real-time quantitative PCR (RT-qPCR). The results indicate that subtoxic concentrations of Ag-NPs may already induce damage of the upper airway epithelial barrier in vitro. The lack of similar disruption by ZnO-NPs of similar size suggests a specific effect by Ag-NPs.